ANALISIS KEBUTUHAN KEPERIBADIAN CARL GUSTAV JUNG PADA TOKOH UTAMA SASA DALAM NOVEL LOVE EDELWISS AND ME KARYA MONICA ANGGEN - Yunis Sastika Putri; Aurellia Khairun Nissa; Eva Dwi Kurniawan (Journal of Student Research, 2024)
The aim of this research is that the researcher wants to analyze more deeply the conscious and unconscious personality dynamics of the main character in the novel entitled "Cinta, Edelweiss and Aku" by Monica Anggen using qualitative descriptive research methods and a literary psychology approach. using Carl's theory of consciousness. Gustav Jung. The formulation of the research problem is, what is the personality structure of the main character Sasa in the novel "Cinta, Edelweiss and Aku" by Monica Anggen? This research shows that the conscious personality structure of the Sasa character is manifested through awareness of what is happening around him, while the unconscious personality structure of the Sasa character is represented through attitudes. , what are the character's personal characteristics and what prevents him from forgetting his ex-boyfriend.